Rucaparib versus standard-of-care chemotherapy in patients with relapsed ovarian cancer and a deleterious BRCA1 or BRCA2 mutation (ARIEL4): an international, open-label, randomised, phase 3 trial. Issue 4 (April 2022) - Kristeleit, Rebecca; Lisyanskaya, Alla; Fedenko, Alexander; Dvorkin, Mikhail; de Melo, Andreia Cristina; Shparyk, Yaroslav; Rakhmatullina, Irina; Bondarenko, Igor; Colombo, Nicoletta; Svintsitskiy, Valentyn; Biela, Luciano; Nechaeva, Marina; et al.
Summary: Background: Few prospective studies have compared poly(adenosine diphosphate-ribose) polymerase (PARP) inhibitors to chemotherapy for the treatment of BRCA1 -mutated or BRCA2 -mutated ovarian carcinoma. We aimed to assess rucaparib versus platinum-based and non-platinum-based chemotherapy in this setting. Methods: In this open-label, randomised, controlled, phase 3 study (ARIEL4), conducted in 64 hospitals and cancer centres across 12 countries (Brazil, Canada, Czech Republic, Hungary, Israel, Italy, Poland, Russia, Spain, Ukraine, the UK, and the USA), we recruited patients aged 18 years and older with BRCA1 -mutated or BRCA2 -mutated ovarian carcinoma, with an Eastern Cooperative Oncology Group performance status of 0 or 1, and who had received two or more previous chemotherapy regimens. Eligible patients were randomly assigned (2:1), using an interactive response technology and block randomisation (block size of six) and stratified by progression-free interval after the most recent platinum-containing therapy, to oral rucaparib (600 mg twice daily) or chemotherapy (administered per institutional guidelines). Patients assigned to the chemotherapy group with platinum-resistant or partially platinum-sensitive disease were given paclitaxel (starting dose 60–80 mg/m 2 on days 1, 8, and 15); those with fully platinum-sensitive disease received platinum-based chemotherapy (single-agent cisplatin or carboplatin, or platinum-doublet chemotherapy). Patients were treated in 21-day or 28-day cycles. The primary endpoint was investigator-assessed progression-free survival, assessed in the efficacy population (all randomly assigned patients with deleterious BRCA1 or BRCA2 mutations without reversion mutations), and then in the intention-to-treat population (all randomly assigned patients). Safety was assessed in all patients who received at least one dose of assigned study treatment. This study is registered with ClinicalTrials.gov, NCT02855944 ; enrolment is complete, and the study is ongoing. Findings: Between March 1, 2017, and Sept 24, 2020, 930 patients were screened, of whom 349 eligible patients were randomly assigned to rucaparib (n=233) or chemotherapy (n=116). Median age was 58 years (IQR 52–64) and 332 (95%) patients were White. As of data cutoff (Sept 30, 2020), median follow-up was 25·0 months (IQR 13·8–32·5). In the efficacy population (220 patients in the rucaparib group; 105 in the chemotherapy group), median progression-free survival was 7·4 months (95% CI 7·3–9·1) in the rucaparib group versus 5·7 months (5·5–7·3) in the chemotherapy group (hazard ratio [HR] 0·64 [95% CI 0·49–0·84]; p=0·0010). In the intention-to-treat population (233 in the rucaparib group; 116 in the chemotherapy group), median progression-free survival was 7·4 months (95% CI 6·7–7·9) in the rucaparib group versus 5·7 months (5·5–6·7) in the chemotherapy group (HR 0·67 [95% CI 0·52–0·86]; p=0·0017). Most treatment-emergent adverse events were grade 1 or 2. The most common grade 3 or worse treatment-emergent adverse event was anaemia or decreased haemoglobin (in 52 [22%] of 232 patients in the rucaparib group vs six [5%] of 113 in the chemotherapy group). Serious treatment-emergent adverse events occurred in 62 (27%) patients in the rucaparib group versus 13 (12%) in the chemotherapy group; serious adverse events considered related to treatment by the investigator occurred in 32 (14%) patients in the rucaparib group and six (5%) in the chemotherapy group. Three deaths were considered to be potentially related to rucaparib (one due to cardiac disorder, one due to myelodysplastic syndrome, and one with an unconfirmed cause). Interpretation: Results from the ARIEL4 study support rucaparib as an alternative treatment option to chemotherapy for patients with relapsed, BRCA1 -mutated or BRCA2 -mutated ovarian carcinoma. Funding: Clovis Oncology.